2014
DOI: 10.1002/ijc.29221
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node count and prognosis in colorectal cancer: The influence of examination quality

Abstract: Colorectal cancer guidelines recommend adjuvant chemotherapy in stage II disease when less than 12 lymph nodes are assessed. The recommendation bases on previous studies showing an association of a low lymph node count and adverse outcome. Compared to current standards, however, the quality of lymph node examination in the studies was low. We, therefore, investigated the prognostic role of <12 lymph nodes in cancers diagnosed adherent to current quality measures. Stage I-IV colorectal cancers from 1,899 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…LNY is an important prognostic factor in patients with stage II–III colorectal cancer, but evidence for stage I colorectal cancer is unclear,,. Although there are studies reporting differences in survival between low and high LNY in patients with Dukes' A/stage I colorectal cancer,, some indicate that LNY alone has no effect on survival outcome. The present study highlights that a substantial number of patients with stage I and II colorectal cancer have a low LNY.…”
Section: Discussionmentioning
confidence: 58%
“…LNY is an important prognostic factor in patients with stage II–III colorectal cancer, but evidence for stage I colorectal cancer is unclear,,. Although there are studies reporting differences in survival between low and high LNY in patients with Dukes' A/stage I colorectal cancer,, some indicate that LNY alone has no effect on survival outcome. The present study highlights that a substantial number of patients with stage I and II colorectal cancer have a low LNY.…”
Section: Discussionmentioning
confidence: 58%
“…This is in accord with a recent population-based study, in which the 12-node benchmark proved to be an independent predictor of CRC in patients with stage I-III disease ( n  = 13,941, HR = 0.67) but not in patients with stage III-IV disease ( n  = 6810, P  = 0.136)24. Another possible reason is that the influence of the LNC on patient survival is more easily diminished by improvements in the quality of external pathology with increasing awareness of the 12-node minimum requirement26. In contrast, the NLNC may be more intrinsically related to enhanced regional lymphocytic reactions that result in an increased NLNC and prolonged survival27.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for higher frequency of more than 12 LNs retrieved in the LNR1 and LNR2 groups compared to LNR0 group is that insufficient lymph node dissection or pathological examination might be performed in the patients with fewer retrieval of LNs, and positive LNs were not dissected or misdiagnosed as negative. Another explanation is that higher immunological reaction may occur in the patients with more aggressive disease, as previous study reported that the frequency of total lymph nodes less than 12 varied by tumor Stage (Stage I: 38%, Stage II and III: 15%) .…”
Section: Discussionmentioning
confidence: 99%